Strategies to Comply with the Kyoto Protocol in Korean Agricultural Sector - 김창길 (한국농촌경제연구원, 2008)
The comprehensive consideration of the internal and external changes in conditions pertaining to the post-2012 Kyoto Protocol scheme indicates that Korea is highly likely to be mandated to reduce greenhouse gas emission from the second commitment period (2013~2017). In the agricultural sector, greenhouse gas emission has been on the decrease, and it also has carbon sinks. Therefore the new emission cut mandate under the Kyoto Protocol to Korea could serve as a good opportunity depending on how we are reacting. This study is a follow-up of the analysis of the impact of the Kyoto Protocol implementation on the agricultural sector and has the purpose of presenting systematic and step-by-step responding strategies in preparation for the implementation of the Kyoto Protocol. In the introduction of the report, the need of the study, purpose and scope of the study, review of literature, and analytic methods are described. Chapter 2 explains the details of the Kyoto Protocol and the implementation mechanism, discussion trends and forecasts of the Post-2012 scheme. Chapter 3 takes a look at the greenhouse gas emission in the agricultural sector and management means. Chapter 4 analyzes the impact of the mandatory greenhouse gas emission cut on the agricultural sector and the potential capability of greenhouse gas reduction by emission cut means. The impact on the agricultural sector is briefly summarized using the result of the first year analysis. Chapter 5 shows the examples of reactions by major countries related to the implementation of the Kyoto Protocol including Japan, Denmark, German, Britain, and the United States. Chapter 6 sets forth the agricultural sector's basic direction of reactions to mandatory reduction, practical strategies, and core tasks. Lastly, Chapter 7 delivers summary and conclusion. The highlights of the study are summarized as follows: First, the participation of the agricultural sector in the emission trading program is found to increase earnings and boost national economy. If carbon tax is imposed, in the short term, facilities plastic vegetable gardening and horticultural sectors, which are highly dependent on fossil fuels, will be put under great pressure of increasing management costs. Second, regarding mandatory emission reduction under the Kyoto Protocol, major countries (Japan, the United States, Denmark, German, and Britain) have marked significant achievements with the agricultural sector's voluntary participation to meet the goal of greenhouse gas reduction. Except for Denmark among the concerned countries, the proportion of the agricultural sector in the greenhouse gas emission is less than 7%, but the agricultural sector takes up a large portion of methane and nitrogen dioxide emission. These countries do not require the agricultural sector to manage their greenhouse gas emission in the form of mandatory requirement. Instead they encourage the agricultural sector to adjust and manage the greenhouse gas generated on the self-regulatory basis. Representative measures taken by the agricultural sector of these countries to cut greenhouse gas emission include facility support, fostering organic farming, utilization of bio-energy, R proper combination between agricultural policy and greenhouse gas reduction policy; active and proactive response to internal and external negotiations; scientific analysis of greenhouse gas emission and absorption volume; and adaptation to global warming. Practical strategies will be in place under the three-step approach by period. The first period of 2008 to 2012 period will lay down the foundation. The second period of 2013 to 2018 will make a leap forward, and the last period of 2019 to 2030 will cement and finalize the achievements obtained so far. Fifth, the core tasks of practical strategies are presented. They include the active pursuit of the 4th comprehensive measures of responding to climate change, the program development for active use of the Kyoto mechanism, the fostering of sound organic farming, continuous effort in the adaptation sector, the systematic R&D efforts, and the establishment of the integrated greenhouse gas management system. Lastly, with the global warming emerging as a hot issue at home and abroad, the agriculture should be recognized as an infrastructure industry for effective management of greenhouse gas emission. To this end, dedicated personnel and organization should be expanded, and proper role sharing and use of experts among related organizations should be sought for active participation in the discussions on national tasks setting for climate change management. The study does not estimate marginal costs by greenhouse gas reduction means and does not determine the priority among policy measures. These areas should be covered by future studies. In addition, an empirical study needs to be conducted to estimate actual reduction volume by applying the economic engineering method and the cost effective analysis by reduction means.